Real-time local impedance monitoring to assess tissue lesion during pulmonary vein isolation: a new tool for AF ablation. (25th November 2020) - Di Cori, A; Segreti, L; Zucchelli, G; Viani, S; Tarasco, F; Barletta, V; Giannotti Santoro, M; Parollo, M; De Lucia, R; Paperini, L; Cellamaro, T; Branchitta, G; et al.
Abstract: Background: Contact force catheter ablation is the gold standard for treatment of atrial fibrillation (AF). Local tissue impedance (LI) evaluation has been recently studied to evaluate lesion formation during radiofrequency ablation. Purpose: Aim of the study was to assess the outcomes of an irrigated catether with LI alghorithm compared to contact force (CF)-sensing catheters in the treatment of symptomatic AF. Methods: A prospective, single-center, nonrandomized study was conducted, to compare outcomes between CF-AF ablation (Group 1) and LI-AF ablation (Group 2). For Group 1 ablation was performed using the Carto 3© System with the SmartTouch SF catheter and, as ablation target, an ablation index value of 500 anterior and 400 posterior. For Group 2, ablation was performed using the Rhythmia™ System with novel ablation catheter with a dedicated algorithm (DirectSense) used to measure LI at the distal electrode of this catheter. An absolute impedance drop greater than 20Ω was used at each targeted. According to the Close Protocol, ablation included a point by point pulmonary vein isolation (PVI) with an Inter-lesion space ≤5 mm in both Groups. Procedural endpoint was PVI, with confirmed bidirectional block. Results: A total of 116 patients were enrolled, 59 patients in Group 1 (CF) and 57 in Group 2 (LI), 65 (63%) with a paroxismal AF and 36 (37%) with a persistent AF. Baseline patients features were not different between groups (P=ns). LI-Group showed a comparable procedural time (180±89 vs 180±56, P=0.59) but with a longer fluoroscopy time (20±12 vs 13±9 min, P=0.002). Wide antral isolation was more often observed in CF-Group (95% vs 80%, P=0.022), while LI-Group 2 required frequently additional right or left carina ablation (28% vs 14%, P=0.013). The mean LI was 106±14Ω prior to ablation and 92.5±11Ω after ablation (mean LI drop of 13.5±8Ω) during a median RF time of 26 [19–34] sec for each ablation spot. No steam pops or complications during the procedures were reported. The acute procedural success was 100%, with all PVs successfully isolated in all study patients. Regarding safety, only minor vascular complications were observed (5%), without differences between groups (p=0.97). During follow up, 9-month freedom from atrial fibrillation/atrial flutter/atrial tachycardia recurrence was 86% in Group 1 and 75% in Group 2 (P=0.2). Conclusions: An LI-guided PV ablation strategy seems to be safe and effective, with acute and mid-term outcomes comparable to the current contact force strategy. LI monitoring could be a promising complementary parameter to evaluate not only wall contact but also lesion formation during power delivery. Funding Acknowledgement: Type of funding source: None